KORELASI MINAT MENONTON FILM MANDARIN DAN BELAJAR MANDARIN PADA MAHASISWA BAHASA MANDARIN ANGKATAN 2016 - Nandasari, Fitria; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractChinese language is one of international languages. In learning Chinese language, students must master the four skills of Chinese language listening, speaking, reading and writing. In order to learn Chinese language more easily, the author has done a research method is to watch Chinese movies. Watching Chinese movies is a happy experience, watching Chinese movies provides a pleasant learning environment. This is will certainly affect the students Chinese learning activities. This research is a correlation between the interest watching Chinese movies and learning Chinese language.This research also involved students of 2016 Chinese language majors from Tanjungpura University as subjects of the research , author interviewed the subject and gave some questionnaire to make research.The results showed that the interest in watching Chinese movies had a strong correlation with learning Chinese language is up to 0.75. Author also find some students who really like watching Chinese movies so their Chinese learning ability is better.Keywords: The Interest Of Watching Chinese Movies, Learning Chinese Language, Correlation Research